2014
DOI: 10.1007/s10503-014-9334-2
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic Argumentation in European Practices of Political Accountability

Abstract: In this paper, the author examines the use of pragmatic argumentation in European practices of political accountability in which the politicians explain and justify a future course of action which they plan to undertake in order to solve an existing problem. The author explains some vital institutional characteristics of the practices under discussion and demonstrates how these institutional characteristics constrain the use of pragmatic argumentation. In addition, the author shows which criteria arguers commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
(16 reference statements)
0
6
0
1
Order By: Relevance
“…Often other aspects are mentioned in the texts such as backing of an expectation or the likelihood of an event and criticism of arguments of other speakers. The previous mentioned papers on pragmatic argumentation suggest such remarks (van Eemeren and Grootendorst (1984), van Eeemeren, Garssen and Meuffels (2009), Andone (2014), van Eemeren (2016 and Andone and Lomeli Hernandez (2019)). Similar remarks can also be found in papers of Erduran et al on argumentation based on Toulmin´s model, for example, the paper of Garcia-Milla, Gilabert, Erduran and Felton (2013).…”
Section: Study Of a Sample Of Decision Arguments Of The Dutch Governmentmentioning
confidence: 92%
See 2 more Smart Citations
“…Often other aspects are mentioned in the texts such as backing of an expectation or the likelihood of an event and criticism of arguments of other speakers. The previous mentioned papers on pragmatic argumentation suggest such remarks (van Eemeren and Grootendorst (1984), van Eeemeren, Garssen and Meuffels (2009), Andone (2014), van Eemeren (2016 and Andone and Lomeli Hernandez (2019)). Similar remarks can also be found in papers of Erduran et al on argumentation based on Toulmin´s model, for example, the paper of Garcia-Milla, Gilabert, Erduran and Felton (2013).…”
Section: Study Of a Sample Of Decision Arguments Of The Dutch Governmentmentioning
confidence: 92%
“…X must be done X highly probably leads to a positive result Y. van Eemeren and Grootendorst (1984), van Eemeren, Garssen and Meuffels (2009), Andone (2014), van Eemeren (2016, and Andone and Lomeli Hernandez (2019) discuss under what conditions such an argument should be acceptable. Several criteria for acceptability have been mentioned such as: that X leads to Y, Y must indeed be positive and X should not have negative side effects that most people would accept result Y and that Y is more desirable than other possible results.…”
Section: Pragmatic Argumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…By answering such anticipated critical questions, a specific argumentative pattern arises which is activated in order to realize the institutional point (van Eemeren and Garssen 2013: 7). In my earlier research on pragmatic argumentation in practices of political accountability (Andone 2015a), I have shown that the result of a prescriptive action is judged as positive when it is shown to be in line with 'the aggregative principle' (Ball 1995: 20). In other words, when it can be shown that carrying out action X is what most people want in the circumstances at hand or is in the interest of the majority.…”
Section: Argumentative Patterns Making Use Of Pragmatic Argumentationmentioning
confidence: 99%
“…Introduction 1 C'est une pratique courante, chez les hommes et femmes politiques, que d'affirmer qu'une mesure particulière doit être mise en oeuvre, qu'une certaine décision doit être prise, ou qu'il faut suivre un programme donné parce que la ligne d'action proposée est susceptible d'avoir des conséquences positives [ou négatives] (« il faut baisser l'impôt sur le revenu pour que les consommateurs puissent acheter davantage de biens »). Pour convaincre leurs partenaires de débat que leur recommandation est acceptable, les politiciens font couramment appel à la majorité (« c'est ce que la plupart des gens veulent en ces temps difficiles ») (Andone 2015). Par de tels appels, les politiciens laissent entendre que leurs actes sont légitimes parce qu'ils traduisent la volonté du peuple (Anderson 1979 : 721).…”
unclassified